Environmental Factors and Lung Function Impairment among Household Industrial Workers of Stone-Carving Crafts at Maritengngae Subdistrict, Sidrap Regency 2016 - Ahmad, Haeranah; Wulandari, Ririn Arminsih (KnE Life Sciences, 2018)
When inhaled by humans, PM2.5 concentrations in the air deposit in the alveoli which can cause inflammation that decreases lung function. Temperature, humidity, and wind speed can affect workplace air pollutants. This cross-sectional study assessed the relationship between environmental factors (PM2.5 concentration, temperature, humidity, and wind speed) and lung function impairment among 100 workers in the Maritengngae subdistrict, Sidrap Regency. Lung function was assessed via spirometry. Temperature, humidity, and wind speed were assessed via a thermohygroanemometer. PM2.5 concentration in the workplace was assessed via a Haz Dust EPAM 5000. Chi-square analysis showed PM2.5 concentration and wind speed had a significant correlation to lung function impairment. Therefore, it should be considered for implementing health and safety programs among workers, monitoring workplace implementation, and performing occupational health surveillance. Keywords: Environmental Factor, Lung Function, Stonecutting Industry